Strategic plan for the Kababayen-an alang sa Teknolohiya nga Haum sa Kinaiyahan ug Kauswagan (KATAKUS) - Esguerra, Michael M.; Soledad, Miguel D.; Pampanga, Dario G. (Davao City School of Management, University of the Philippines Mindanao, 2010)
According to David (1997) strategic management can be defined as the art and science of formulating, implementing, and evaluating cross-functional decisions that enables an organization to achieve its objective.
According to David (1997) strategic management can be defined as the art and science of formulating, implementing, and evaluating cross-functional decisions that enables an organization to achieve its objectives. Handmade paper has a rich, colorful history which has spanned the world?s geography and its cultures. It is widely used for its eco friendly nature and the traces of history are left in different cultures. The handmade paper craft of KATAKUS, Inc. is a joint undertaking with a peasant women organization in Brgy. Katipunan, Panabo City that begun in 1996. The project manufactures handmade paper products made from fibers of abaca, banana bracts and durian husks. The papers are converted into various novelty items such as cards, albums, scrapbooks, lamps, picture frames, and boxes. The handmade paper project produces quality products that are uniquely made out of the combination of other indigenous materials such as abaca/romblon twines, sinamay (weaved abaca fiber), coconut wood, bamboo leaves and twigs, fossilized leaves, and pressed flowers, weeds/grasses. In order to evaluate the accomplishment of KATAKUS, where it is now and where it is heading, the paper used the strategic management framework. This helped assess the internal strengths and weaknesses of the organization as well as opportunities in faces in relations to its external environment. Using the Internal Factor Evaluation (IFE) Matrix, the organization scored 2.37 which means that it has a weak internal position. On the other hand, using the External Factor Evaluation (EFE) Matrix, KATAKUS scored 2.90 which imply that it has an average ability to respond to changes in its external environment. In view of the existing corporate objectives, it was proposed that there be a separate vision, mission statements and goals for its social enterprise program, the handmade paper craft. The Quantitative Strategic Planning Matrix (QSPM) which is designed to help determine the relative attractiveness of feasible alternative strategies indicated the advisability of implementing the following strategies for KATAKUS, Inc: market development, market penetration, product development, and joint ventures. These strategies are aligned to increase net sales revenue, decrease production cost, and acquire new equipment and fund from donor agencies. Lastly, feedback and evaluation of programs are crucial in the implementation of strategy, for small and medium enterprise. Thus, a system to relay vital to the implementation of the above strategies is also recommended to report on activities and progress so as to provide a basis for basis for managerial decision making.
Thesis,Graduate (Master in Management)--University of the Philippines Mindanao, December 2010.